High systemic immune-inflammation index is associated with carotid plaque vulnerability: New findings based on carotid ultrasound imaging in patients with acute ischemic stroke - Zhang, Lianlian; Lyu, Qi; Zhou, Wenyan; Li, Xia; Ni, Qinggan; Jiang, Shu; Shi, Guofu (Frontiers in Neurology, 2022)
Abstract--Vulnerable carotid plaque is closely related to to the occurrence of Ischemic stroke. Therefore, accurate and rapid identification of the nature of carotid plaques is essential. AS is a chronic immune inflammatory process. Systemic immune inflammation index (SII) is a novel index of immune inflammation obtained from routine whole blood cell count analysis, which comprehensively reflects the state of inflammation and immune balance in the body. This study sought to explore the relationship between SII level and carotid plaque vulnerability, plaque composition characteristics and acute ischemic stroke (AIS) severity. A total of 131 patients diagnosed with AIS presenting with carotid atherosclerotic plaque were enrolled in this study. Using carotid ultrasound (CDU) to assess carotid responsible plaque properties, we divided the patients into stable plaques group and vulnerable plaques group, and analyzed the correlation between SII levels and plaque vulnerability. And further analyzed to evaluate the correlation between high SII levels and plaque characteristics and AIS severity. In addition Cohen’s Kappa statistics was used to detect the consistency of Carotid ultrasound (US) and cervical High-resolution magnetic resonance imaging (HRMRI) in evaluating plaque vulnerability. The findings showed that the vulnerable group had higher levels of SII compared with the stable group. The high SII group had more vulnerable plaques and high frequency of plaque fibrous cap rupture compared with the low SII group. Logistic analysis showed that high SII level was an independent risk factor for vulnerable plaques (odds ratio [OR] = 2.242) and plaque fibrous cap rupture (OR=3.462). The results also showed a high consistency between Carotid US and HRMRI methods in assessment of plaque vulnerability (Cohen's kappa value was 0.89 (95% CI=0.78~0.97)) and the level of SII was positively associated with NIHSS score (r=0.473, P<0.001) . Our study suggests that elevated levels of SII may have adverse effects on vulnerability of carotid plaques, especially in stroke patients with vulnerable plaques with ruptured fibrous caps, which may aggravate the severity of AIS. Keywords: Carotid ultrasound, Systemic immune inflammation index, Acute ischemic stroke, Vulnerable plaque, High-resolution magnetic resonance imaging.